Variations In The Use Of Indonesian In Social Media: A Case Study On Tiktok - Hidayanti, Ni Nyoman Ayu Tri; Sucipta, I Made Darma (Program Studi Magister Pendidikan Bahasa dan Sastra Indonesia, Program Pascasarjana, Universitas Pasundan Bandung, 2024)
This study discusses the use of Indonesian language variations in TikTok social media. TikTok as a social media application that can provide education and entertainment, there are many unique and creative variations of language in it. This research discusses the variations of Indonesian in it and the impact of language variations in TikTok. This research method uses qualitative analysis methods. The technique used is listening and note-taking techniques to obtain data by listening to language use and noting the language in the speech. The research findings show that there are many variations in Indonesian, including the use of mixed Indonesian with regional languages, changes in words, and changes in meaning in the creator's speech.